THE DEVELOPMENT OF CLASS-BASED ASSESSMENT TO MEASURE STUDENT CRITICAL THINKING ON CHEMICAL LEARNING USING THE CONTEXTUAL TEACHING AND LEARNING MODEL - Nahadi, Nahadi; Siswaningsih, Wiwi; Fadilla, Sarah (Universitas Kuningan, 2018)
The purpose of this study was to obtain class-based assessment instrument that can measure the critical thinking skills of students in learning chemistry using a model of contextual teaching and learning . The research method used is a research and development (R D) with the design of the study one group pretest-posttest. The study was conducted on 34 students of class X at one of the public high schools in Bandung with the object of research in the form of assessment tools consisting of critical thinking skills test consisting of 15 multiple choice questions grounded, 3 pieces of essays, and 6 pieces of matter worksheets, observation sheet, guidance interviews, and questionnaires . The results showed that the multiple choice questions have reasoned highest validity deduce indicators and consider the results of deduction,Â low reliability, level of difficulty between easy to difficult , and significant distinguishing features. Essay has the highest validity indicators ask and answer questions with high reliability, moderate difficulty level, and significant distinguishing features. Student Worksheet has the highest validity indicators ask and answer questions with very high reliability, level of difficulty between easy to moderate, and significant distinguishing instrument developed to measure students' critical thinking skills about the views of validity, with the highest validity of multiple choice questions grounded is number 4 and 13, the highest validity essay is number 1a and 1b, and the highest validity LKS numbers 1, 2, and 3. Contextual teaching and learning can be supportive in improving students' critical thinking skills that can be seen from curiousity stages through observation sheet.Keywords: class-based assessment; critical thinking skills; contextual.